2008
DOI: 10.1038/jhh.2008.156
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, blood pressure and osteoporosis

Abstract: Both hypertension and osteoporosis have common underlying nutritional aetiology, with regards to dietary cations intake. We tested the hypothesis that sodium intake reflected in urinary Na/Cr and blood pressure would be negatively associated with bone mineral density (BMD), whereas other cations may have opposite associations. Subjects were part of a study of bone health in 4000 men and women aged 65 years and over. A total of 1098 subjects who were not on antihypertensive drugs or calcium supplements and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
2
19
2
2
Order By: Relevance
“…Vegetables showed a weaker association with BMD or osteoporosis than fruit in this study and in previous studies [6, 35], possibly because that vegetables are often consumed in cooked form in Chinese populations and the high intake of sodium with vegetables might accelerate calcium excretion [36] and offset the possible benefit of vegetables. Besides, vegetables were typically cooked by stir-frying, boiling, or steaming in China.…”
Section: Discussioncontrasting
confidence: 57%
“…Vegetables showed a weaker association with BMD or osteoporosis than fruit in this study and in previous studies [6, 35], possibly because that vegetables are often consumed in cooked form in Chinese populations and the high intake of sodium with vegetables might accelerate calcium excretion [36] and offset the possible benefit of vegetables. Besides, vegetables were typically cooked by stir-frying, boiling, or steaming in China.…”
Section: Discussioncontrasting
confidence: 57%
“…High sodium diets have been shown to alter calcium metabolism 47 and to increase bone resorption in postmenopausal women. 48 Conversely, low sodium diets have been shown to be protective of bone health 49 by reducing bone turnover and improving calcium balance. 50 Sodium phosphate salts, also found in processed foods and cheeses, have been shown to increase serum parathyroid hormone levels, which is unfavorable to bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The clinical risk factors must be validated in order to be combined with BMD. For example, in our study we found that some risk factors, such as inadequate protein intake [42] and high sodium intake, [43] occur quite frequently in Turkish postmenopausal patients, but these risk factors remain unvalidated for our population. In addition, heavy alcohol intake in postmenopausal women is an extremely rare occurrence in our population.…”
Section: Discussionmentioning
confidence: 90%